Foreign Direct Investment in the tourism sector: the case of France - Cró, Susana (2020)
This study investigates the determinants of inward Foreign Direct Investment (FDI) stock in the French hospitality industry. A panel gravity model is applied to bilateral inward FDI stock between France and nineteen investor countries in Hotels and the Restaurant industry over 2000–2017. Results show that bilateral inward FDI stocks between France and investor countries are positively affected by their income and are inversely proportional to the distance between them. It is also found that differentials between France and the investing countries in terms of taxes, labour costs, abundance of skilled labour, supply of public goods and total FDI stock also play a significant role in understanding the foreign location decisions. Finally, the results show that France is particularly successful in attracting FDI in the hospitality industry from French-speaking countries with a common border and cultural proximity to France.